Design Optimization And Improvement Of 6S-10P Outer-Rotor AlCiRaF PMFSM Using Finite Element Analysis - Jenal, Mahyuzie; Thayir, Mohamed Hariz; Aziz, Roziah; Sulaiman, Erwan; Ahmad, Zarafi (Evolution in Electrical and Electronic Engineering, 2021)
Alternate circumferential and radial flux (AlCiRaF) is a new proposed design in permanent magnet flux switching machine (PMFSM). Even though AlCiRaF PMFSM offers high torque and power density it is however produces high cogging torque compared to other types of FSM. To deal with this problem, continuous research and development on electric machines should be applied to improve the cogging torque drawback. In this research, 6 slots 10 pole AlCiRaF PMFSM by employing outer rotor, E core shape of armature coil, permanent magnet in radial and circumferential shape is to study and compare the performance of initial outer rotor design and optimized outer rotor design in the term of torque performances. The optimized design will be evaluated by varying eight types of main parameters to observe which design gives better output torque. Initially, design procedures of AlCiRaF PMFSM including parts drawing, material and condition setting, the properties setting are all explained. Then, coil arrangement test is conducted to perform 3 phase armature coil arrangement. Then, no load analysis is conducted to analyses cogging torque, flux linkage, flux distribution and back-EMF of motor followed by load analysis which analyses the torque speed characteristics and output power of the motor. No load analysis and load analysis are conducted using finite element analysis of JMAG Designer 16.1. Finally, the best parameter for all main parts have been obtained. As a conclusion, at the end of this chapter will summary all about the results of studies that have been conducted.